Comparison of two modes of inducing potentiation of sprint cycling performance - Carney, B.; Kelly, L. A.; Lamont, H. (Journal of Athletic Enhancement, 2016)
Background: The use of Post-activation potentiation (PAP) techniques is becoming increasingly popular prior to power-based sports training and competition. A Wingate cycle test is widely used to measure work and power output during short, high-intensity bouts.